2017
DOI: 10.1158/1078-0432.ccr-16-1203
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Alpha-Fetoprotein (AFP)–MHC Complex with CAR T-Cell Therapy for Liver Cancer

Abstract: This study demonstrates that CAR T-cell immunotherapy targeting intracellular/secreted solid tumor antigens can elicit a potent antitumor response. Our approach expands the spectrum of antigens available for redirected T-cell therapy against solid malignancies and offers a promising new avenue for liver cancer immunotherapy. Clin Cancer Res; 23(2); 478-88. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
120
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(126 citation statements)
references
References 43 publications
0
120
0
Order By: Relevance
“…Recently, Nishio et al (2014) have overcome the obstacle through inoculating intratumorally with an armed oncolytic virus which effectively attracted CAR‐T cells to the tumor site. In addition, it is reported that directly intratumorally administered CAR‐T cells could generate a potent and long‐lasting antitumor immune response (Adusumilli et al, 2014; H. Liu et al, 2017; Pituch et al, 2018; Priceman et al, 2018). Several related clinical trials of intratumoral immunization are in research phase (Table 5).…”
Section: In Situ Antitumor Vaccination With Immune Cellsmentioning
confidence: 99%
“…Recently, Nishio et al (2014) have overcome the obstacle through inoculating intratumorally with an armed oncolytic virus which effectively attracted CAR‐T cells to the tumor site. In addition, it is reported that directly intratumorally administered CAR‐T cells could generate a potent and long‐lasting antitumor immune response (Adusumilli et al, 2014; H. Liu et al, 2017; Pituch et al, 2018; Priceman et al, 2018). Several related clinical trials of intratumoral immunization are in research phase (Table 5).…”
Section: In Situ Antitumor Vaccination With Immune Cellsmentioning
confidence: 99%
“…Other groups are exploring the possibility of local delivery, to enhance tumor killing and to reduce toxicity. Indeed, it has been shown that regional administration of anti-AFP or anti-CEA CAR T cells was equally effective or even superior to a systemic administration in xenograft models of peritoneal carcinomatosis (106,107), and the delivery of CAR T cells through percutaneous hepatic artery infusions has shown to be safe and clinically active in patients with CEA-expressing liver metastases (108). A different approach to favor the localization into the tumor site consists in the administration of CAR T cells overexpressing tumorspecific chemokine receptors enhancing their capacity of reaching the tumor tissues (109).…”
Section: Car T Cells For Solid Tumorsmentioning
confidence: 99%
“…The results of several clinical trials testing CARs and transgenic TCRs, particularly in patients with hematological malignancies, demonstrated that these engineered T cells are robust tools for cancer treatment (Almåsbak, Aarvak, & Vemuri, ; Eshhar, ; Kalos, ; H. Liu et al, ; Lu et al, ; Smith, Oertle, Warren, & Prato, ). One of the primary considerations in designing genetically modified T cells is selecting a tumor‐restricted target (Smith et al, ).…”
Section: Therapeutic Biomarkers In Car T‐cell Therapymentioning
confidence: 99%